Review on Practical Guidance of Veterinary Clinical Diagnostic Approach - Tagesu Abdisa (International Journal of Veterinary Science and Research - Peertechz Publications, 2017)
Animal disease problems have been investigated by veterinarians through undertaking a careful and clinical examination with the objective of recognizing the nature of the affection.So,that effective treatment and control measure is adopted.Clinical examination is one of the fundamental for diagnosing animals  which are presented to clinic.Veterinary clinical examination relies on knowledge of Anatomy,Physiology, Pathology and Animal behavior, skills in the methods and techniques of clinical examination,clinical sign  and pathogenesis of the diseases which are the basic requirements for clinician in his/her good  diagnostic approach.The diseased animals which are presented to veterinary clinic can be analyzed by  veterinarian or clinician,the clinician approach through asking the owners complaint,which request for  professional assistance by giving animal history.The accurate and complete history of patient may get from focusing on collection of patient data, present, past and environmental history in appropriate to patient animals.The veterinarian can approach to animals by the method of restraining in order to handle in  safe condition.Physical examination is the examinations that apply to animals by general inspection,  palpation,percussion and auscultation methods used to detect clinical signs of abnormalities.Clinical  examination can be undergone by taking vital sign, general clinical examination and systemic examination  of animals.Animals which have been diagnosed by veterinarian may have medication,through the injection or oral route with an appropriate dose of drug related to body weight,age and condition of animals.In conclusion,the veterinary clinical diagnostic approach is the core and the most important to generate accurate clinical examination,investigation of animal's disease problem and guide how to handle the animals and the methods of restraining of animals.The objective of this review paper is helps to understand and know how the procedure of veterinary clinical diagnostic undergoes and treatment of animals takes place, to guide and give knowledge on systemic and general examination of domestic animals